Shearer Newcastle's greatest no. 9 (Kuala Lumpur : Idaman Sari Trading, 2000)
Captain of England, the world's most expensive footballer, top scorer in Euro'96 and for three consecutive easons in the premier League...Alan Shearer is unquestionably one of the greatest footballers of all time
VCD format
Keywords: Sports films; Sport in motion pictures